2018
DOI: 10.1002/chem.201705818
|View full text |Cite
|
Sign up to set email alerts
|

Metallothermic Reduction of Silica Nanoparticles to Porous Silicon for Drug Delivery Using New and Existing Reductants

Abstract: Abstract:In this study, the influence of metals (Mg, Al, and Ca) and reaction conditions (time, temperature, and metal grain size) on the metallothermic reduction of Stöber silica nanoparticles (NPs) to form porous Si was explored. Mg metal was found to be an effective reducing agent even at temperatures below its melting point; however, it also induced a high degree of structural damage and morphology change. Al was effective at reducing silica NPs only at its melting point and higher temperatures, but the re… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
27
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 33 publications
(28 citation statements)
references
References 77 publications
0
27
0
Order By: Relevance
“…This effect is determined to be from a higher degree of structural damage of the template at higher temperatures. 52 2.2.3 Reaction time. The reaction time for reduction varies between studies with durations reported from 30 minutes 45 up to 12 hours.…”
Section: Ramp Ratementioning
confidence: 99%
See 2 more Smart Citations
“…This effect is determined to be from a higher degree of structural damage of the template at higher temperatures. 52 2.2.3 Reaction time. The reaction time for reduction varies between studies with durations reported from 30 minutes 45 up to 12 hours.…”
Section: Ramp Ratementioning
confidence: 99%
“…Increasing the magnesium grain size from ne powder (À325 mesh), chips (4-30 mesh) and foil have shown to decrease the reduction rate, caused by the improper mixing of the reactants. 52 The mixing of the reactants by a ball milling process can provide enough kinetic energy to reach the reaction ignition point, and has been used to perform the magnesium reduction. This method has also been scaled up to a 5 litre scale in an attrition mill.…”
Section: Ramp Ratementioning
confidence: 99%
See 1 more Smart Citation
“…Metallothermic reduction reaction (MRR) of silica to silicon has been studied over the past decade [24][25][26][27][28]. This technique has gained a lot of attention because of the low cost involved, lower temperature, and the ready availability of metals such as magnesium and aluminum.…”
Section: Introductionmentioning
confidence: 99%
“…The magnesiothermic reduction of silica nanoparticles has been reported to increase the surface area from 8.2 m 2 g −1 to 386 m 2 g −1 after a 12-h reaction time at 500 • C. Pore volume also increased from 0.07 cm 3 g −1 to 1.7 cm 3 g −1 . The surface area of silicon particles produced by aluminothermic reduction was a magnitude smaller than the magnesium-reduced product, with the greatest surface area reported as 37 m 2 g −1 after 24 h at 650 • C. Pore volume was determined to be 0.51 cm 3 g −1 after 12 h at 650 • C. Transmission electron microscopy (TEM) images of the porous substrate showed that a aluminothermic reduction produces a less porous substrate than magnesiothermic reduction, with the porous silicon composed of layers [105].…”
Section: Metalothermic Reductionmentioning
confidence: 97%